Comparison of Psoriasis Area and Severity Index (PASI) Scores in Patients Treated with Oral Methotrexate and A Combination of Oral Methotrexate and Narrow Band-Ultraviolet B (NB-UVB) Phototherapy - Ervina Rosmarwati; Nurrachmat Mulianto; Bobby Febrianto; Dita Eka Novriana; Siti Efrida Fiqnasyani (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Psoriasis Vulgaris is an autoimmune disease characterized by chronic skin inflammation and epidermal hyperplasia. Psoriasis Area Severity Index (PASI) score is one of the assessments to measure the psoriasis severity. Oral methotrexate is one of the effective therapies for psoriasis patients. Narrow Band-Ultraviolet B (NB-UVB) phototherapy is an adjunctive psoriasis therapy given concurrently with oral methotrexate. Purpose: Determine the difference in Psoriasis Area Severity Index (PASI) scores between Psoriasis Vulgaris patients treated with oral methotrexate and a combination of oral methotrexate and NB-UVB phototherapy. Methods: This observational analytic study was conducted at the Dermatology and Venereology Clinic, Dr. Moewardi General Hospital Surakarta. The patients received oral methotrexate and a combination of oral methotrexate and and Narrow Band-Ultraviolet B (NB-UVB) phototherapy. A retrospective study of medical records was conducted to determine the patient's PASI score before the therapies and 3 months after. All data were analyzed with the Shapiro Wilk normality test and the independent T-test. A p-value was <0.05, and it was considered significant. Result: The mean of decreased PASI scores in the oral methotrexate group was (6.00 +2.47) and (6.08 +2.17) in the combination therapy group. Based on the statistical test results from the 24 subjects, it was found that the PASI score decreased (p=0.931). Conclusion: There was no significant difference in the decrease in PASI between the oral methotrexate group and the combination therapy group. The mean reduction of PASI scores was more significant in the combination therapy than in the methotrexate group